2020
DOI: 10.21203/rs.3.rs-22745/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TUG1 as ceRNA combined with miR-29a to promotes the expression of IFITM3 in hepatocellular carcinoma

Abstract: Background: Numerous studies have shown that TUG1 has an important relationship with tumorigenesis. TUG1 is highly expressed in most tumors and can promote tumor development. However, the role of TUG1 in hepatocellular carcinoma (HCC) remains to be studied. miR-29a plays a tumor suppressor role in a variety of tumors, and there is a relationship between TUG1 and miR-29a, but the specific relationship and mechanism of action are still unclear. miR-29a can inhibit the expression of IFITM3. However, the regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Zhu et al showed that lncRNA HULC promotes HCC cells proliferation by functioning to sponge and downregulate miR-29 [ 60 ]. A preprint report conducted by Liu et al showed that lncRNA TUG1 competitively targets miR-29a to upregulate the expression of a oncogenic factor, interferon-induced transmembrane protein 3 (IFITM3), resulting in increased proliferation, invasion, and migration of HCC [ 61 ]. In addition, Qu et al identified that lncRNA HOXA-AS3 acts as a tumor-promoting factor in gastric cancer cells by suppressing miR-29a, leading to the activation of lymphotoxin β receptor (LTBR)/NF-κB signaling [ 62 ].…”
Section: Molecular Sponges Targeting Mir-29a: Cernasmentioning
confidence: 99%
“…Zhu et al showed that lncRNA HULC promotes HCC cells proliferation by functioning to sponge and downregulate miR-29 [ 60 ]. A preprint report conducted by Liu et al showed that lncRNA TUG1 competitively targets miR-29a to upregulate the expression of a oncogenic factor, interferon-induced transmembrane protein 3 (IFITM3), resulting in increased proliferation, invasion, and migration of HCC [ 61 ]. In addition, Qu et al identified that lncRNA HOXA-AS3 acts as a tumor-promoting factor in gastric cancer cells by suppressing miR-29a, leading to the activation of lymphotoxin β receptor (LTBR)/NF-κB signaling [ 62 ].…”
Section: Molecular Sponges Targeting Mir-29a: Cernasmentioning
confidence: 99%